Diversity, difference and Caribbean feminism : the challenges of anti-racism - Reddock, Rhoda (2007)
Analyzes the changing ways which feminist activists of the Anglophone Caribbean women's movement have addressed issues of 'race' and ethnicity. Examines how they have interacted, negotiated, and created alliances and coalitions or sought to challenge hierarchies and divisions in their everyday praxis. Explores also the anti-racist work of feminist activists at the end of 20th century in the context of Trinidad and Tobago and Guyana at the high point of the Caribbean Women's movement in the 1980s and 1990s.